Effects of defect action level of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) fragments on quality of wheat flour. (21st June 2021) - Negi, Aditi; Pare, Akash; Manickam, Loganathan; Rajamani, Meenatchi
Abstract: BACKGROUND: Tribolium castaneum (Herbst) is one of the most important secondary storage pests of all types of flour and flour‐based products. The present study focuses on the fragment producing behaviour of T. castaneum in wheat flour during storage and its effect on the quality parameters and defect action level (DAL) of fragments. The US Food and Drug Administration has set a DAL of 75 insect fragments in 50 g of flour. Box–Behnken design was used to optimize the storage conditions (storage period in days and temperature in degrees Celsius) and insect density (numbers) to keep insect fragments below the DAL. RESULTS: Optimization results indicated that the presence of single number of adult of T. castaneum is enough to cross the DAL of insect fragments within a storage period of 21 days at a storage temperature of 30 °C. Insect fragments cause perceptible changes in the quality of wheat flour. When sample attained DAL of T. castaneum fragments in wheat flour, the various quality parameters were analysed in that moisture content of wheat flour was 10.8 ± 0.26%, total colour change was 2.052 (Δ E value), T. castaneum progeny emergence was 19.66 ± 1, uric acid was 1.8 ± 0.16 g kg −1 and microbial count was 7.34 ± 0.5 cfu g −1 . CONCLUSIONS: Results from the present study indicate that the presence of even a single adult of stored pest in wheat flour should not be ignored. It is mandatory to determine the threshold level and frequent sampling is required to achieve zero tolerance of stored product insects in food commodities. © 2021 Society of Chemical Industry.